A importância do incentivo ao desenho infantil - Crespo, Laiz Rossini [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The present work's objective is to analyze the benefits of drawing for child development, encouraging children to draw. By doing this research, we want to prove the strengths that drawing can bring to the life of a child in areas such as emotional, intellectual, social, perceptual and motor development, seeking ways to encourage drawing for children. This research is bibliographic and focuses on authors like Viktor Lowenfeld, Robert Read, Edith Derdik, Georges-Henri Luquet, Ana Mae Barbosa and others who advocate drawing as a significant form of expression for child development

O presente trabalho teve como objetivo analisar os benefícios do desenho para o desenvolvimento infantil, do estímulo à criança para desenhar. Com essa pesquisa pretendeu-se, demonstrar as virtudes que o desenho pode trazer para a vida da criança em âmbitos como, o desenvolvimento emocional, intelectual, social, perceptual e motor, buscando maneiras de incentivar o desenho infantil. Essa pesquisa tem caráter bibliográfico e focaliza autores como Viktor Lowenfeld, Robert Read, Edith Derdik, Georges- Henri Luquet, Ana Mae Barbosa entre outros que defendem o desenho como forma de expressão significante para o desenvolvimento infantil
Keywords: Educação pre-escolar; Arte e educação; Desenho infantil; Crianças - Desenvolvimento